Formic acid decomposition on clean and pre-adsorbed (O,C and N) surface of Cu (100) catalyst - Zhang, Shurui (2009)
In this work, effect of pre-adsorbed impurities (O, C and N) on binding energies of adsorbates on Cu (100) surface was investigated using DFT method. It was found that H2COO was affected significantly at all positions of impurities. Favorability of reaction routes was also looked into, and results showed that on both clean and pre-adsorbed surfaces, release of H from H2CO, through the formation of H2COO and HCOO, was the most feasible pathway in terms of reaction energy.